Influence Of Magnetic Field On The Electrodeposition Of Ni-Co Alloy - Ebadi, M.; Alias, Y.; Basirun, Wan Jefrey (Indian Academy of Sciences, 2010)
The electrodeposition of Ni-Co alloy from a nickel Watt's solution in the absence and presence of a permanent parallel magnetic field (PPMF) to the plane of deposition (perpendicular to direction of current) produced a deposited layer with mostly fine grain structure. The deposited layers have been characterized by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX). It was found that the mass deposition rate with PPMF was greater than the deposition in the absence of PPMF, where the rate of difference electrodeposited mass (Delta m) was calculated (Delta m = 0.07 to 0.12 mg cm(-2)min(-1)). In the presence of PPMF, the electrodeposition of cobalt was high (0 to 5%) compare to the absence of PPMF. The corrosion resistance of Ni-Co alloy layers fabricated by PPMF proved higher than without PPMF.